Photomedicine - Advances in Clinical Practice 2017
DOI: 10.5772/65344
|View full text |Cite
|
Sign up to set email alerts
|

Low Level Energy Photodynamic Therapy for Skin Processes and Regeneration

Abstract: Skin is the largest human organ and displays multiple functions involving structure and protection against external agents that may affect the body. Solar radiation accelerates the normal aging process and may even cause great damage leading to many different cutaneous diseases and skin cancer. Moreover, a wound in the skin may be an open channel for the access of pathogens usually exposing blood vessels for infections and causing serious complications. For many reasons, regulatory skin processes are of great … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 72 publications
(108 reference statements)
0
25
0
1
Order By: Relevance
“…Our results agree with those of previous studies showing that a lower light dose is beneficial for cell migration and wound healing. 5,27,28 Tedesco and Jesus used the photosensitizer silicon-naphthalocyanine in a liposomal formulation and irradiation with a laser at 670 nm with low light doses of 0.5, 1, 3, and 5 J/cm 2 on an ex vivo human skin model. 27 They found that low-dose (1 J/cm 2 ) PDT prevented elastic network degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results agree with those of previous studies showing that a lower light dose is beneficial for cell migration and wound healing. 5,27,28 Tedesco and Jesus used the photosensitizer silicon-naphthalocyanine in a liposomal formulation and irradiation with a laser at 670 nm with low light doses of 0.5, 1, 3, and 5 J/cm 2 on an ex vivo human skin model. 27 They found that low-dose (1 J/cm 2 ) PDT prevented elastic network degradation.…”
Section: Discussionmentioning
confidence: 99%
“…5,27,28 Tedesco and Jesus used the photosensitizer silicon-naphthalocyanine in a liposomal formulation and irradiation with a laser at 670 nm with low light doses of 0.5, 1, 3, and 5 J/cm 2 on an ex vivo human skin model. 27 They found that low-dose (1 J/cm 2 ) PDT prevented elastic network degradation. An even lower light dose (0.07 J/cm 2 ) initiated the formation of new collagen, as reported by the same authors.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular identity should not be explained in the clinical report of the patient. This therapy status statistically important quantitative molecular variation related to the modified appearance of the dermis 70 . Hence, it gives the promise of repairing and reproducing and may useful diagnosis for the skin aging in the future.…”
Section: Photodynamicmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a versatile therapeutic technique that has been successfully applied throughout the years in cancer treatment [ 1 , 2 , 3 , 4 , 5 ], aged related macular degeneration [ 3 , 6 ] and in the inactivation of microorganisms (antimicrobial PDT = aPDT) under clinical and non-clinical contexts [ 7 , 8 , 9 , 10 ]. More recently, the possibility of exploring the approach for improving wound healing/tissue regeneration after a traumatic lesion is attracting the attention of several research groups [ 11 , 12 , 13 , 14 , 15 ]. The localized response to PDT treatment varies according to the conditions in which this therapeutic approach is applied, where a photosensitizer (PS) molecule/drug with the ability to absorb visible light is placed in direct contact with the target tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the light parameters and on the PS structure, different levels of ROS can be produced [ 16 ]. Such ROS levels can be toxic enough to promote in situ (1) cancerous cell destruction [ 16 , 17 , 18 ] or (2) pathogenic microorganism inactivation, namely, of multidrug-resistant strains [ 12 , 19 , 20 , 21 , 22 ], or in a level, able to induce cell proliferation and tissue regeneration ( Figure 1 ) [ 11 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%